Aristotle's determination of the skill of household management in the polis: About the original dispute between economics and politics - Zoran Dimić (Economic Themes, 2022)
The first systematic definition of economics in Western culture takes place in Aristotle's Politics. In the first chapter of this writing, Aristotle analyzes in detail the skill of household management (economics). When he tries to see the same skill not only within the household, but also in the context of the political community (polis), Aristotle notices problems that arise with the development of the skill of acquiring property (κτητικὴ) and the skill of acquiring wealth (χρηματιστικήν). The application of the principle of household management to the political community leads to fundamental problems, fundamentally unsolvable, due to which the economy and politics in the political community (polis) remain in permanent tension.
Keywords: N00; B30; D1; 330; economy; household; politics; dispute; management; wealth